Differential diagnosis of orofacial pain III: associated with neuropathic disorders - Acosta-Ortiz, Rodolfo (Revista Facultad de Odontología Universidad de Antioquia, 2020)
This is the last of three articles that have the purpose of presenting a literature review of the conditions that have been considered to establish the differential diagnosis of different orofacial pain conditions (OFP). In this article, neuropathic disorders both episodic (trigeminal neuralgia, glossopharyngeal neuralgia, occipital neuralgia) and continuos (neuritis, postherpetic neuralgia, deafferentation pain, and atypical pain) are discussed. Throughout these articles, the main clinical characteristics of the different orofacial pain conditions have been presented. Those characteristics are used to make a systematic comparison with the clinical finding of the patient, which will provide the basis to establish the correct differential diagnosis. Therefore, independent of knowing the treatment, the clinician should be familiar with as many clinical characteristics of the different orofacial pain conditions as possible.